2022
DOI: 10.3390/ijms231911582
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer RNA (eRNA) in Human Diseases

Abstract: Enhancer RNAs (eRNAs), a class of non-coding RNAs (ncRNAs) transcribed from enhancer regions, serve as a type of critical regulatory element in gene expression. There is increasing evidence demonstrating that the aberrant expression of eRNAs can be broadly detected in various human diseases. Some studies also revealed the potential clinical utility of eRNAs in these diseases. In this review, we summarized the recent studies regarding the pathological mechanisms of eRNAs as well as their potential utility acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 164 publications
(225 reference statements)
0
3
0
Order By: Relevance
“…ERNA is a type of non-coding RNA, that is transcribed from enhancer regions. eRNA has been shown to play a significant role in the activation of oncogenes and aberrant signaling pathways, which contribute to tumorigenesis 19 , 20 . Several studies have demonstrated that oncogene-induced eRNAs can directly promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…ERNA is a type of non-coding RNA, that is transcribed from enhancer regions. eRNA has been shown to play a significant role in the activation of oncogenes and aberrant signaling pathways, which contribute to tumorigenesis 19 , 20 . Several studies have demonstrated that oncogene-induced eRNAs can directly promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Schmidt (2001) showed that beehives marked with synthetic Nasonov pheromone were more attractive to honeybees and Mayer, Britt et al, 1989, Mayer, Johansen et al (1989) found that NGP increased honeybee visitation and fruit set in apple, cherry and pear in the USA. In China, the application of NGP lures increased the honeybee visitation frequency and fruit set in blueberry (Liu et al, 2016) and sweet cheery (Wang et al, 2021). However, in orchards without beehives pear flower visitation rates were low, despite the 27.6‐fold higher flower visitation rates in trees with NGP lures than without NGP lures (1.38 ± 0.96 vs. 0.05 ± 0.05 visits per 40 min).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, eRNA has multiple regulatory functions, such as mediating the formation of enhancer-promoter loops, maintaining an open chromatin state, changing the chromatin spatial conformation, and recruiting RNAP2 and other transcription initiation complex molecules [ 13 , 15 17 ]. In recent years, the important biological functions of eRNAs have just began to be unraveled in the regulation of diseases, such as cancer, neurodegenerative diseases, cardiovascular diseases, and metabolic diseases [ 18 ]. Therefore, comprehensively analyzing the role of eRNAs, as a hub in integrating signaling from upstream transcription factors (TF) to regulate downstream target genes, would significantly contribute to understanding the genetic basis of complex traits.…”
Section: Introductionmentioning
confidence: 99%